Technical Training on Replacement of R410a with R290 in Split Air Conditioners as an Effort to Reduce Global Warming for BLK Instructors in Karawang Regency - Ismail Wellid; Bowo Yuli Prasetyo; Sugiyarto; Muhamad Anda Falahuddin; Sumeru; Andriyanto Setyawan (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Earth's surface temperature continues to rise due to the emission of gases that have a very high GWP (Global Warming Potential). One gas that has a very high GWP is R410A refrigerant, which is 2088. This refrigerant is still widely used in split air conditioners (A/Cs). Therefore, the use of R410A must be immediately reduced and replaced with a more environmentally friendly refrigerant, R290, which only has a GWP value of 3. One of the initial efforts to socialize the use of R290 as a substitute for R410A in split A/Cs was to provide socialization in theory and practice to instructors at the Karawang Regency Vocational Training Centre. A good understanding of environmentally friendly refrigerants by the instructors is expected to be transmitted to the job seekers who are trained and will later be in the business of installing and servicing split A/Cs. Based on direct interviews with the instructors who participated in this socialization and technical guidance, they felt enlightened and motivated to help the government program to reduce emissions of gases that cause global warming. The replacement of R410A refrigerant in split air conditioners with R290 reduced the total global warming impact, i.e. the TEWI (Total Equivalent Warming Impact) value decreased by 31.91%.